Interictal and Ictal MEG in presurgical evaluation for epilepsy surgery - Stefan, Hermann; Rampp, Stefan (Acta Epileptologica, 2020)
Although presurgical evaluation of patients with pharamacoresistent focal epilepsies provides essential information for successful epilepsy surgery, there is still a need for further improvement. Developments of noninvasive electrophysiological recording and analysis techniques offer additional information based on interictal and ictal epileptic activities. In this review, we provide an overview on the application of ictal magnetoencephalography (MEG). The results of a literature research for published interictal/ictal MEG findings and experiences with own cases are demonstrated and discussed. Ictal MEG may provide added value in comparison to interictal recordings. The results may be more focal and closer to the invasively determined seizure onset zone. In some patients without clear interictal findings, ictal MEG could provide correct localization. Novel recording and analysis techniques facilitate ictal recordings. However, extended recording durations, movement and artifacts still represent practical limitations. Ictal MEG may provide added value regarding the localization of the seizure onset zone but depends on the selection of patients and the application of optimal analysis techniques.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Ictal MEG; Interictal MEG; Localization of epileptic activity; Presurgical evaluation